Thermally stimulated conductivity of Cu 3BiS 3 thin films deposited by co-evaporation: Determination of trap parameters related to defects in the gap (2012)
thin films were produced by evaporating precursor Cu and Bi species in sulfur atmosphere through a two-stage process. Thermally stimulated current (TSC) measurements were carried out on as-grown Cu3BiS3 crystals in the temperature range of 150–400 K. The measurements were performed while increasing temperature at a rate of 5 K/min. Analysis of thermal power measurements at room temperature enabled the type of conductivity of the material, respectively. The spectra obtained from the TSC showed the presence of trapping centers associated with the peaks in the current curves as a function of temperature. Transport mechanisms as hopping and thermally active carriers were identified for low- and high-temperature regions, respectively. Three trapping levels around 1.04 eV were detected from the TSC spectra. These levels in Cu3BiS3 crystals may be associated to the presence of structural defects and unintentional impurities during preparation processes. The trap parameters were determined by various analysis methods, and they agree well with each other. A correlation between electrical properties and defects in the material were also studied.